Konsep dan Contoh Aplikasi Konseling Religius dengan Pendekatan Takziyah Al-Nafs - Dita Angraini; Wenda Asmita (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2022)
Religious counseling is an effort to integrate religious values into the teaching and counseling process. This article provides the concept of religious counseling with a soul-cleansing approach, or Tazukiya Al Nafs. The concept proposed by Al-Ghazali is counseling or spiritual healing based on moral sufistic principles. Tazkiyah al-Nafs is the process of purifying the soul from all vices or morals of the psalm that exists in a person with the aim of healing oneself from prisoners from various diseases by realizing the various Achlaqul Karimah. and literature research, in which various reference sources are analyzed and analyzed to arrive at a synthesis that can be considered reasonable and logical with what has been tested. Up. Tazkiyah al-Nafs' approach includes not only the field of psychoanalysis related to defense mechanisms, but also cognitive, behavioral, and spiritual counseling, so it can be used as a counseling technique or approach, and the approach can be applied to the counseling process. Keywords: religious counseling; tazkiyah al-nafs